A Systematic Review of Challenges in Fog Computing (International Journal of Innovative Research in Computer Science & Technology, 2021)
The number of Internet of Things (IoT)  applications is rapidly increasing. Current cloud-centric IoT  designs, on the other hand, are unable to meet the mobility  and dormancy necessities of duration precarious IoT  practices. In certain industries, the practices have hampered  the expansion of IoT. The computation in the Fog model is  investigated in the present study as an option for IoT  applications. Fog computing problems or obstacles for IoT  applications must be thoroughly reviewed and synthesized.  This study uses a well-known and commonly used method of  systematic literature review (SLR) technique to address this  critical research requirement. From an initial collection of  439 publications, 17 relevant studies were selected and  examined by means of the SLR method and specific  searching conditions generated from the study topic. In  addition, four papers were hand-selected based on the  significance to the topic. The collected information from the  review was divided into a set of primary difficulty groups.  The verdicts of the presented study may assist practitioners  and scholars in better understanding fog computing  problems, as well as providing a variety of valuable acumens for upcoming research. Range or scope of the study mainly is restricted to collection of the resources that have been  evaluated from the database.
Keywords: Architecture; Computing in Cloud; Fog Computing; Internet of Things (IoT); Operational Process.